Perspectives for the linking city. The digital transformation of Kigali and the challenges of re-building a nation with technology - (:unkn) unknown (My University, 2021)
Perspectives for the linking city. The digital transformation of Kigali and the challenges of rebuilding a nation with technology. Paper presented at the 2021 "Linking City" Conference, Netexplo/UNESCO, April 14-15, 2021 Brice Laurent (CSI / Mines ParisTech) Is Kigali still an African city? A little more than one million inhabitants live in Kigali, the capital of Rwanda, after years of population growth and spatial extension of the city. But Kigali's fame does not reflect its relatively small size, or that of Rwanda itself. Praised as the "cleanest city in Africa", Kigali is described in numerous media and popular accounts as a success story, a globally visible illustration of how to move from a troubled past to a promising future, and the demonstration that African cities can be innovative sites of global relevance. The interest for Kigali maps onto that for Rwanda, a small landlocked country in central Africa where growth rates have been steady for the past few years and well above many other African countries 1. It is primarily the country's capital that has become an international point of attention, and indeed a global hub fit for entrepreneurship, and attractive to foreign investors and tourists. Numerous media accounts describe newest additions to the city skyline, such as the hive-like Convention Centre inspired by a traditional hut called irongo used by Rwanda's pre-colonization rulers, and marvel at the livability of a hilly and green city where spotless streets lead to technological hubs and innovation centers 2. Across the Internet,
Keywords: African Research